Gambaran perilaku orang tua dalam menjaga kesehatan gigi dan mulut anak usia 6-12 tahun selama masa pandemi covid-19 : (kajian pada sd islam al-amanah kabupaten bandung) - Satelina Salsabila, Citra; Dwimega, arianne; Widhianingsih, Dhyani (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Dental and oral disease could cause health-burdening issues affecting a person his entire life. The COVID-19 pandemic is forcing people to stay at home while at the same time resulting in a decrease care of teeth, such as the lowering habit of brushing teeth twice a day, and doing routine checks every 6 months to the dentist. Objective: To describe the behavior of parents in maintaining dental and oral health of children aged 6-12 years at Al-Amanah Islamic Elementary School, Bandung Regency during the COVID-19 pandemic. Methods: Descriptive observational research with quantitative data types. This research was conducted using a cross-sectional approach. A total of 106 respondents of parents at Al-Amanah Islamic Elementary School in Bandung Regency were tested using a questionnaire-based measuring instrument in the form of a google form. The analysis was conducted using univariat analysis with SPSS. Results: The research results are categorized into three behavioral aspects, namely knowledge, attitude and action. Based on the results of data calculations, in the aspect of knowledge, there are 95 respondents in the good category or 89.62%, and 11 respondents in the sufficient category or 10.38%. Meanwhile, in the attitude aspect, there are 26 respondents in the good category or 24.53%, 79 respondents in the sufficient category or 74.53%, and 1 respondent in the poor category or 0.94%. In the action aspect, there are 82 respondents in the good category or 77.36%, 23 respondents in the sufficient category or 21.70%, and 1 respondent in the poor category or 0.94%. Conclusion: Overview of parental behavior in maintaining dental and oral health of children aged 6-12 years during the COVID-19 pandemic at Al-Amanah Islamic Elementary School, Bandung Regency, mostly has a good category.